Knowledge and utilisation of climate information services and climate smart agriculture for climate readiness and one-health in Ghana - Mponela, Powell; Damba, Osman Tahidu; Yeboah, Stephen; Kofituo, Rich Kofi; Odoi, Maureen Erekua; Dalaa, Mustapha Alasan (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Adaptation to climate change is happening on several fronts. The study was commissioned to capture gender dynamics in climate information services, climate smart agriculture technologies, and climate-smart one–health interventions for promoting social inclusion and informing policy in Ghana’s food systems. The study regions were selected based on previous evidence of impacts of climate change generated by Climate Change and Food Security (CCAFS) project. The study therefore, takes stock of existing practices, information channels and their impacts to inform further research and development.